Barrier-function-based distributed adaptive control of nonlinear CAVs with parametric uncertainty and full-state constraint - Zhu, Yang (2020)
The platoon control of connected and automated vehicles (CAVs) is an emerging problem and has become a hot topic in transportation research. Most of the existing results are based on second-order or third-order linear vehicular dynamics. They ignore either the actuator internal kinetics or vehicular inherent nonlinearity, and the linearization requires a complete priori knowledge of plant parameters and may not be easy to implement in practice. In order to overcome these shortcomings, this paper concentrates on third-order nonlinear vehicular plants with parametric uncertainty and full-state constraint. Different from the popular linear-matrix-inequality (LMI) robust control and model predictive control (MPC), this paper proposes a barrier-function-based distributed adaptive backstepping control scheme. The third-order nonlinear vehicle models are considered, uncertain parameters are identified on-line, full-state constraints are not violated, and the tracking control objectives are established. Simulation studies are carried out to verify the effectiveness of the developed control design.